Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1159/000119868
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Extrathymic Generation of Regulatory T Cells Specific for a Retinal Antigen

Abstract: Background: Thymic expression of a photoreceptor cell antigen, interphotoreceptor retinoid-binding protein, is known to generate regulatory T cells (Treg) that prevent spontaneous autoimmune disease of the retina. However, the contribution of other endogenous, tissue-specific antigens (Ags) expressed in the retina to the generation of Treg is uncertain. Methods: Transgenic mice that express β-galactosidase (β-gal) in photoreceptor cells, together with β-gal-specific T cell receptor transg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Previously, we found that an ONC reversed the inhibitory activity of the endogenous regulatory response to retinal βgal in the ear-swelling assay for DTH (38). The ONC injures a small fraction of retinal neurons, stimulating an increase in the number of retinal GFP + DC and their activation, as detected by upregulation of MHC class II expression.…”
Section: Resultsmentioning
confidence: 88%
“…Previously, we found that an ONC reversed the inhibitory activity of the endogenous regulatory response to retinal βgal in the ear-swelling assay for DTH (38). The ONC injures a small fraction of retinal neurons, stimulating an increase in the number of retinal GFP + DC and their activation, as detected by upregulation of MHC class II expression.…”
Section: Resultsmentioning
confidence: 88%
“…However, this DTH response was inhibited in naïve arrβgal × βgalTCR double Tg mice, but the inhibition could be overcome in these mice by antibody depletion of CD25 + cells prior to ear testing (Fig. 2A ) [41]. We have also obtained similar results with a CD4 + TCR Tg and a CD8 + TCR Tg (both specific for distinct βgal epitopes) crossed with arrβgal mice, all on the B6 background (unpublished observations).…”
Section: Retinal Ags Induce a Distinct Immunoregulation Mediated By Cmentioning
confidence: 57%
“…This differs from ACAID immunoregulation which is associated with increased levels of all three cytokines. Further, splenocytes from B10.A and arrβgal mice that were subjected to βgal-induced ACAID and then βgal immunized were blocked in their production of IL-2 and IFN-γ upon antigenic challenge, whereas βgal immunized arrβgal mice could only induce a partial reduction in IFN-γ levels compared to B10.A controls [41]. Second, the expression of βgal in photoreceptors is different than the placement of a bolus of Ag.…”
Section: Retinal Ags Induce a Distinct Immunoregulation Mediated By Cmentioning
confidence: 99%
See 1 more Smart Citation
“…• Can we expect that intravitreal therapy will control an immune-mediated disorder – when specific (circulating) immune cells are considered to be important [1]?…”
Section: Introductionmentioning
confidence: 99%